PERANCANGAN SISTEM HR-WELLBEING: PANDUAN INTERVENSI DIGITAL DAN PENGUKURAN KINERJA TERINTEGRASI KESEJAHTERAAN KARYAWAN - Anip Febtriko; Tri Rahayuningsih; Nelia Afriyeni (LPPM Universitas Abdurrab, 2026)
Digital transformation in the workplace demands that organizations build human resource management systems that integrate employee productivity and well-being. Findings on the High Wellbeing and Performance Work System (HWBPWS) demonstrate that psychological, social, and workplace well-being play a crucial role in driving sustainable performance. This study aims to design an HR-Wellbeing System, a digital model that combines well-being intervention guidance with an integrated individual performance measurement system based on the dimensions of Employee Well-Being (EWB) and Individual Work Performance (IWP). This study employs a Research and Development (R&D) method, encompassing needs analysis, system prototype design, and integration of well-being and performance measurement instruments. Data were collected through literature reviews, instrument readability tests, and expert validation regarding system design and indicator suitability. The results demonstrate that the designed system is capable of providing digital intervention features in the form of psychoeducational modules, self-reflection, burnout and presenteeism indicators, and a performance analytics dashboard connected to employee well-being data. This integration makes it easier for organizations to monitor HR conditions in real-time and carry out more targeted interventions in a humane and data-based manner. In conclusion, the HR-Wellbeing System can be a strategic innovation in modern HR practices, providing a sustainable digital approach to improving employee well-being and performance in various organizational sectors, including the public and private sectors that are adapting to HR 5.0.